PSYCHOLOGICAL SELF-JUSTIFICATION OF CRUEL ACTS IN AGATHA CHRISTIE’S NOVEL AND THEN THERE WERE NONE - Nasution, Cherry Adistya; Wulan, Sri (JOURNAL OF LANGUAGE, 2025)
The study analyzes Judge Wargrave’s psychological mechanisms of self-justification in Agatha Christie’s And Then There Were None. Using a descriptive qualitative approach, the analysis identifies Wargrave’s self-justification, defense mechanisms, and manipulative behaviors as strategies to rationalize his cruelty. His sadistic obsession and obsessive ambition reveal the complexity of moral reasoning behind his actions. The study contributes to understanding human rationalization of unethical behavior through a literary-psychological lens.The analysis was carried out by categorizing some information into two themes of diccussion. The first theme is the protagonist’s three actions to justify his cruel act: self-justification, self-defense mechanisms, and manipulation. Then, the second theme is the protagonist’s two reasons to do cruel act: sadistic obsession and insane ambition. The results of this study indicate that Judge Wargrave uses various psychological mechanisms to justify his cruel actions. By looking at the psychological and literary context, this research provides an understanding of human nature and behavior, which shows the psychological complexity of the protagonist to uphold justice in an unethical way.